Difference Expressions CD34 in Acute Myeloid Leukemia Cell Culture in the Administration of Cytarabine-Daunorubicine Dose Standards - Muhammad Saiful Rahman; Paulus Budiono Notopuro; Suprapto Ma'at; Made Putra Sedana; Arifoel Hajat (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
The cure rate for patients with Acute Myeloid Leukemia (AML) is 20-75%. Standard-dose cytarabine + (SDAC)-daunorubicine gives a remission rate of ± 60%, and the case of relapse is frequently found. In-vivo CD34 expression is a reliable and straightforward test that must evaluate AML patients' response to predict the response of chemotherapy + induction phase accurately. Differences in in-vitro CD34 expression are expected to be able to predict chemosensitivity in AML patients. An experimental post-test-only control group study was conducted from May to December 2019, and 8 AML subjects were found. Peripheral Blood Mononuclear Cells (PBMC) were isolated from peripheral blood samples of patients with AML collected in EDTA tubes. The PBMC isolated from peripheral blood were divided into two groups, and each group contained 106 PBMC cells in culture media. The control group (without treatment) and the SDAC-daunorubicine group were 0 + incubated for 4 hours at 37 C with a 5% CO2 atmosphere. The expression of CD34 was measured using FACSCaliburâ„¢, while + CD34+ percentage was calculated with CellQuestâ„¢ software. The percentage of CD34 in the control, SDAC + DNR, showed a significant difference with p < 0.001. This study showed a significant difference between the control group and the group + administered with the standard dose of cytarabine-daunorubicine with p < 0.001. The average CD34 expression in the + SDAC-DNR treatment group was higher than in the control group. CD34 markers cannot be used as predictors of chemosensitivity in the administration of chemotherapy.